2001
DOI: 10.1021/la001391y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrophobically Modified Polymers and Surfactant Lamellar Phase

Abstract: We investigate the effect of polysoaps on the phase behavior and membrane elastic properties of the lyotropic lamellar (LR) phase of the nonionic surfactant penta(ethylene glycol) dodecyl ether (C12E5). The polysoap is a hydrophobically modified polymer (hm-polymer) with n-alkyl side groups randomly grafted to a polyacrylate (PAA) backbone. The membrane properties are extracted from small-angle neutron scattering data based on a model developed by Nallet et al. and the excess area method developed by Roux et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 37 publications
6
78
0
Order By: Relevance
“…4a and 4b. In mixed membranes of hydrophobically modified polymers and nonionic surfactants, it has been found that if the radius of gyration of polymer is comparable to or greater than one half of the interlamellar distance, phase separation into two co-existing lamellar phases generally occurs [40,41].…”
Section: Microstructure Of Liquid Crystalsmentioning
confidence: 99%
“…4a and 4b. In mixed membranes of hydrophobically modified polymers and nonionic surfactants, it has been found that if the radius of gyration of polymer is comparable to or greater than one half of the interlamellar distance, phase separation into two co-existing lamellar phases generally occurs [40,41].…”
Section: Microstructure Of Liquid Crystalsmentioning
confidence: 99%
“…Although not yet reported for other quaternary systems, polymer-induced formations of two coexisting L α phases were also observed in ternary systems, i.e., water-surfactantamphiphilic block copolymer [27][28][29][30]. For example, Yang et al found that the addition of hydrophobically modified polyacrylates to the binary system H 2 O-C 12 E 5 induces the formation of one vesicular and two L α phases [27].…”
Section: A 2 H Nmr Study Of the Phase Diagrammentioning
confidence: 99%
“…For example, Yang et al found that the addition of hydrophobically modified polyacrylates to the binary system H 2 O-C 12 E 5 induces the formation of one vesicular and two L α phases [27]. Kunieda and coworkers added the above-mentioned long-chain A-B silicone surfactant Si 25 C 3 E 51.6 to the system H 2 O-C 12 E 5 and found a polymer-containing L α phase in coexistence with a polymerfree lamellar phase, which is denoted L α in [28].…”
Section: A 2 H Nmr Study Of the Phase Diagrammentioning
confidence: 99%
“…hydrophobically modied polymers like PAA or PEG; 4,[11][12][13][14] amphiphilic poly(ethylene propylene)-poly(ethylene oxide) added to bicontinuous microemulsions; 10,15,16 and a triblock-peptide added to a lamellar phase.…”
Section: Introductionmentioning
confidence: 99%